PENGARUH BIAYA PROMOSI PENJUALAN DAN BIAYA PERIKLANAN TERHADAP PENJUALAN HANDPHONE PADA UD.ONE WAY CELL DI KOTA DENPASAR - Ni Ketut Karwini; Jesslyn Monika Sallie (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
This study is intended to determine the effect of sales costs and advertising costs on mobile phone sales. Type This research is a causality research with sales promotion cost and advertising cost as independent variable and sales as dependent variable. Methods of data collection using observation methods, interviews, and documentation. Data analysis used in this research use classical assumption test, multiple linear regression, F test, and t test.The results of this study found that the cost of sales promotion partially have a positive and significant impact on mobile phone sales. Meanwhile, advertising costs showed no significant positive effect.Therefore, the company still performs the cost of selling promotions effectively so that it can increase the sales of mobile phones, which in turn will attract potential buyers.